Maternal and Newborn Thyroid Hormone, and the Association With Polychlorinated Biphenyls (PCBs) Burden: The EHF (Environmental Health Fund) Birth Cohort - Berlin, Maya; Barchel, Dana; Brik, Anna; Kohn, Elkana; Livne, Ayelet; Keidar, Rimona; Tovbin, Josef; Betser, Moshe; Moskovich, Miki; Mandel, Dror; Lubetzky, Ronit; Ovental, Amit; et al. (Frontiers in Pediatrics, 2021)
Background: Polychlorinated biphenyls (PCBs) are ubiquitous environmental contaminants found in human tissues. PCBs can be transferred through the placenta and may disrupt the maternal thyroid homeostasis, and affect fetal thyroid hormone production. Several studies have shown that intrauterine exposure to PCBs might be associated with abnormal levels of thyroid hormones in mothers and their offspring. Objectives: To examine the associations between environmental exposure to PCBs and thyroid hormone levels in mothers and newborns. Methods: The EHF-Assaf-Harofeh-Ichilov cohort includes 263 mothers-newborns dyads. A total of 157 mother-newborn dyads had both PCBs and thyroid function measures. Regression models were used to estimate associations between maternal PCB exposure and maternal and newborn thyroid function, controlling for possible confounders. Results: Four PCBs congeners were analyzed: PCBs 118, 138, 153, and 180. ∑PCBs median (IQR) level was 14.65 (2.83-68.14) ng/g lipids. The median maternal thyroid-stimulating hormone (TSH) level was 2.66 (0.70-8.23) µIU/ml, the median maternal free thyroxine (FT4) level was 12.44 (11.27-13.53) µg/dL, the median maternal thyroid peroxidase antibodies (TPO Ab) level was 9.6 (7.36-12.51) IU/mL. Newborns' median total thyroxine (T4) level was 14.8 (7.6-24.9) µg/dL. No association was found between exposure to different congeners or to ∑PCBs and maternal TSH, FT4, thyroglobulin autoantibodies (Tg Ab), TPO Ab and newborn total T4 levels. In multivariable analysis a 1% change in ∑PCBs level was significantly associated with a 0.57% change in maternal TSH levels in women with body mass index (BMI) <19. The same association was observed for each of the studied PCB congeners. Maternal TPO Ab levels statistically significantly increased by 0.53% and 0.46% for 1% increase in PCB 118 and 153 congeners, respectively. In women with BMI>25, the association between the PCBs levels and maternal TSH levels was in the opposite direction. No association was found in women with normal BMI (19-24.9). Conclusions: Background exposure to environmentally relevant concentrations of some PCBs can alter thyroid hormone homeostasis in pregnant women and might be associated with abnormal TSH levels and TPO-Ab in women with low BMI. However, these findings require further investigation.